Modulation of microRNA Activity by Semi-microRNAs - Plante, Isabelle; Plé, Hélène; Landry, Patricia; Gunaratne, Preethi H.; Provost, Patrick (Frontiers in Genetics, 2012)
The ribonuclease Dicer plays a central role in the microRNA pathway by catalyzing the formation of 19 to 24-nucleotide (nt) long microRNAs. Subsequently incorporated into Ago2 effector complexes, microRNAs are known to regulate messenger RNA (mRNA) translation. Whether shorter RNA species derived from microRNAs exist and play a role in mRNA regulation remains unknown. Here, we report the serendipitous discovery of a 12-nt long RNA species corresponding to the 5’ region of the microRNA let-7, and tentatively termed semi-microRNA, or smiRNA. Using a smiRNA derived from the precursor of miR-223 as a model, we show that 12-nt long smiRNA species are devoid of any direct mRNA regulatory activity, as assessed in a reporter gene activity assay in transfected cultured human cells. However, smiR-223 was found to modulate the ability of the microRNA from which it derives to mediate translational repression or cleavage of reporter mRNAs. Our findings suggest that smiRNAs may be generated along the microRNA pathway and participate to the control of gene expression by regulating the activity of the related full-length mature microRNA in vivo.